The influence of consumer ethnocentrism on purchase of domestic fruit and vegetables in Portugal: Application of the extended theory of planned behaviour - Miguel, L.; Marques, S.; Duarte, A. P. (British Food Journal, 2022)
Purpose – With the crescent globalisation together with economic and food crisis, consumers are increasingly confronted with food products from different origins and appeals to consume “national”. One factor influencing the purchase behaviour of domestic food products is the consumer ethnocentrism. The aim of this paper is to study consumers’ purchase behaviour intention towards “produce in Portugal” fruit and vegetables applying a consumer ethnocentrism extended model of the Theory of Planned Behaviour (TPB). Design/methodology/approach – A questionnaire was presented to a sample of 700 Portuguese consumers responsible for the household food purchase by computer assisted telephone interview system. Structural equation modelling was conducted to examine direct and indirect effects of consumer ethnocentrism via attitude, subjective norm, and perceived behavioural control on consumer intention to purchase domestic fruit and vegetables. Findings – Findings suggest that consumer ethnocentrism both directly and indirectly influences purchase intention. Consumer ethnocentrism reinforces consumers’ attitudes and perceived behavioural control regarding the purchase of domestic fruit and vegetables, thereby increasing their intention to purchase such products in the future. TPB model is applicable in determining the consumers' intention to buy domestic fruit and vegetables in Portugal. Research limitations/implications – This study provides the food industry and retail with informative basis about which mechanisms underlie the consumers’ intention to buy domestic fruits and vegetables. New food categories should be studied. Originality/value – This study gives a first insight on Portuguese consumer ethnocentric tendencies. Moreover, it contributes to the globally ongoing discussion about the relevance of consumer ethnocentrism for determining purchase behaviour by identifying TPB components as relevant mediating mechanisms of consumer ethnocentrism effects on purchase intention.